The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18632/oncotarget.27910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cell microenvironment on the drug sensitivity of hepatocellular cancer cells

Abstract: The native hepatocellular cancer (HCC) microenvironment is characterized by more hypoxic, hypoglycemic, and acidic conditions than those used in standard cell culture. This study aimed to investigate whether HCC cells cultured in more native conditions have an altered phenotype and drug sensitivity compared to those cultured in standard conditions. Six HCC cell lines were cultured in “standard” (21% O 2 , 25 mM glucose) or more “native” (1% O 2 , 5 mM glucose, 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It has been reported that urease can inhibit the development of human breast cancer and lung cancer by inducing extracellular pH alkalization [108]. Since the activity of immune cells can be inhibited by the acidification of microenvironment, the occurrence and development of tumor can be slowed down by using buffer to neutralize tumor acidosis and then immunotherapy, which has been reported in the literature as an effective method [109]. In addition, it has been reported that the progression of liver cancer can be slowed by inhibiting the activities of glycolic-related enzymes such as glucose transporter, hexokinase, pyruvate kinase, and 6-phosphofructokinase [12,14,16,17].…”
Section: Perspectives Of Liver Cancer Therapy From Tumor Acidic Micro...mentioning
confidence: 99%
“…It has been reported that urease can inhibit the development of human breast cancer and lung cancer by inducing extracellular pH alkalization [108]. Since the activity of immune cells can be inhibited by the acidification of microenvironment, the occurrence and development of tumor can be slowed down by using buffer to neutralize tumor acidosis and then immunotherapy, which has been reported in the literature as an effective method [109]. In addition, it has been reported that the progression of liver cancer can be slowed by inhibiting the activities of glycolic-related enzymes such as glucose transporter, hexokinase, pyruvate kinase, and 6-phosphofructokinase [12,14,16,17].…”
Section: Perspectives Of Liver Cancer Therapy From Tumor Acidic Micro...mentioning
confidence: 99%
“…Interestingly, however, while this review mentions the evidence of hypoxia (6 mmHg median tumor pO2 compared to 30 mmHg median pO2 in normal liver tissue) in the tumor type "liver" (Table 2 in [42]), the original literature cited in support of this statement did not determine the partial pressure of oxygen in human HCC, but in liver metastases of rectal cancer [14,15]. Thus, the particular use of the terms "liver" and "tumor type" in McKeown's review ("secondary liver tumor" would have been more accurate) led the authors of several articles to (incorrectly) conclude that hypoxia is a typical feature of HCC [43][44][45][46][47]. The review by McKeown had several other flaws: (a) the lack of correct units for pO2 (% instead of mmHg, Torr or kPa), (b) inappropriate use of Henry's law and Dalton's law (both are only valid for gas mixtures or gases dissolved in homogeneous solutions), and (c) the assumption that Bunsen's solubility coefficient α and Henry's law constant H are valid for heterogeneous tissues (Note: 𝛼 greatly depends on the water and lipid contents of a tissue, the volume of the extravascular space, etc.…”
Section: Critical Evaluation Of Data On the Existence Of "Severe Hypoxia In Hcc"mentioning
confidence: 99%
“…The tumor microenvironment influences several oncogenic processes such as immune evasion, tumor proliferation, metastasis and drug resistance [ 115 , 116 , 117 ]. These processes are modulated by tumor architecture and vasculature, interaction with normal and immune cells, cytokine release, altered cellular signaling and gene expression due to an acidic and hypoxic milieu, and the dysregulation of essential metabolites such as glucose and lactate [ 118 , 119 , 120 , 121 , 122 , 123 ].…”
Section: Tumor Microenvironment and Heteroplasmymentioning
confidence: 99%
“…These processes are modulated by tumor architecture and vasculature, interaction with normal and immune cells, cytokine release, altered cellular signaling and gene expression due to an acidic and hypoxic milieu, and the dysregulation of essential metabolites such as glucose and lactate [ 118 , 119 , 120 , 121 , 122 , 123 ]. For example, hepatocarcinoma cells cultured under hypoxic conditions (1% O 2 , 5 mM glucose, 10 mM lactate) showed an increase in the number of mutations in mtDNA and an overexpression of glycolytic enzymes such as hexokinase 2 ( HK2 ) and glucose transporter ( GLUT ), in comparison with cells cultured under standard conditions (21% O 2 , 25 mM glucose) [ 116 ].…”
Section: Tumor Microenvironment and Heteroplasmymentioning
confidence: 99%